2019
DOI: 10.1002/app.47525
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nonsolvent additives on PES ultrafiltration membrane pore structure

Abstract: Sponge-like pore (cellular pore) structure of ultrafiltration membrane has special advantages on rejection and anti-pressure performance. The cover by Lei Zhang and colleagues shows a SEM image of spongelike pore structure of PES UF membrane, which was prepared by adding some non-solvent additives. The membrane with fully sponge-like structure retained good operation stability for long time at high pressure. Inevitably, the permeate flux was decreased because of greater mass transfer resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Therefore, the residual DMAc content of the membrane can be analyzed in terms of the N content. In past studies, it has been demonstrated that hydrophilic additives may accelerate the phase inversion process 39–41 . It can be observed by XPS spectrogram that the elemental N content decreased significantly with increasing TA addition, which indicated that TA was able to diffuse more DMAc into the water coagulation bath.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the residual DMAc content of the membrane can be analyzed in terms of the N content. In past studies, it has been demonstrated that hydrophilic additives may accelerate the phase inversion process 39–41 . It can be observed by XPS spectrogram that the elemental N content decreased significantly with increasing TA addition, which indicated that TA was able to diffuse more DMAc into the water coagulation bath.…”
Section: Resultsmentioning
confidence: 93%
“…In past studies, it has been demonstrated that hydrophilic additives may accelerate the phase inversion process. [39][40][41] It can be observed by XPS spectrogram that the elemental N content decreased significantly with increasing TA addition, which indicated that TA was able to diffuse more DMAc into the water coagulation bath. The decrease in DMAc content may be attributed to the ability of hydrophilic TA to promote phase inversion during the membrane production process, which allowed more DMAc to enter the coagulation bath.…”
Section: Composition and Structural Analysis Of Pes/ta Membranesmentioning
confidence: 99%
“…Due to its importance in membrane production, phase inversion process has been studied to determine the influence of different variables in the final morphology [7][8][9][10] . In these studies, different formation mechanisms were proposed to explain the formation of macrovoids, a cellular morphology, and interconnected structure and the dense layer.…”
Section: Introductionmentioning
confidence: 99%